Percentage of Broiler Carcass Pieces Age of 5 Weeks That Given Turmeric Powder in Drinking Water - B. A., Widnyana; Astawa, I P. A.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2019)
ABSTRACT This study aims to determine the effect of giving turmeric powder through drinking water towards the percentage of broiler commercial carcass pieces aged of 5 weeks. The research was executed in a cage owned by Mr. I Ketut Arcana located in Candi Kusuma, Melaya, Jembrana Village for 40 days. The study was carried out using a completely randomize design (CRD) consisting of three treatments, namely: broiler given drinking water without turmeric powder (A), broiler given turmeric powder 0.5g/lt drinking water (B), and broiler given turmeric powder 1g/lt drinking water (C). Each treatment consisted of five replications and each replication used 12 broiler chickens age of 1 week regardless of sex with an average body weight of 179.33 ± 12.56 g. The variables observed were sloughter weight, carcass weight, carcass percentage, and percentage of carcass pieces. After 5 weeks, the result showed that the administration of tumeric powder in drinking water by 0.5g and 1g significalty (P<0.05) increase slaughter weight, carcass weight, and percentage of carcass pieces on breast, but the result of carcass weight in level 0.5g not significalty (P>0,05), then carcass percentage and percentage of carcass pieces of back, thighs, drum stick, and wings not significantly affect (P>0,05). Based on the result of this study it can be concluded that the administration of tumeric powder through drinking water by 1g can increase slaughter weight, carcass weight, and percentage of carcass pieces on breast, but not effect on carcass percentage and of carcass pieces of back, thighs, drum stick, and wings of broiler 5 weeks. Keywords : turmeric powder, broiler chicken, percentage commercial carcass pieces.